PENGEMBANGAN AGRIWISATA PUNCAK TEMBOAN DI RURUKAN SATU KECAMATAN TOMOHON TIMUR - Mentari D. Mamarodia; Oktavianus Porajow; Caroline B.D. Pakasi; Melisa L.G. Tarore (COCOS, 2015)
ABSTRACTMentari Dwitika Mamarodia, The development of Puncak Temboan Agritourism in Rurukan Satu village, East Tomohon Sub District (underguidance of Oktavianus Porajow as a chairman, Caroline B. D. Pakasi and Melissa Tarore as members).The objective of this research is to identify and analyze descriptively agritourism development in Puncak Temboan Rurukan Satu village. The study was conducted over six months starting January to in July 2014. The data used in this study were primary data obtained from interviews and questionnaires to the respondents, Tomohon Municpality Tourism Agency, farmer groups GEMA AGAPE as manager and tourists. The secondary data were obtained Rurukan Satu village. The data were analyzed descriptively and presented in tabular form.The research result showed that the Agritourism Puncak Temboan was not well developed. It can be seen from the unfulfilled elements of attractions, facilities and infrastructure at the agritourism location.